2016
DOI: 10.1542/peds.2015-4387
|View full text |Cite
|
Sign up to set email alerts
|

Safety Profile of the 9-Valent HPV Vaccine: A Combined Analysis of 7 Phase III Clinical Trials

Abstract: The overall safety profile of the 9-valent human papillomavirus (9vHPV) vaccine was evaluated across 7 Phase III studies, conducted in males and females (nonpregnant at entry), 9 to 26 years of age. METHODS:Vaccination was administered as a 3-dose regimen at day 1, and months 2 and 6. More than 15 000 subjects received ≥1 dose of 9vHPV vaccine. In 2 of the studies, >7000 control subjects received ≥1 dose of quadrivalent HPV (qHPV) vaccine. Serious and nonserious adverse events (AEs) and new medical conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 40 publications
11
101
1
3
Order By: Relevance
“…The final formulation of this vaccine contains L1-based VLPs from the 9-valent HPV serotypes mostly associated with the development of cervical cancer. 23 Recombinant vaccines produced in yeast strains other than S. cerevisiae (so-called non-conventional strains) are of great interest for production of vaccine antigens and immunotherapeutics. One such non-conventional strain is Pichia pastoris, a yeast originally introduced in the 1960s as an additive for animal foods, and later, thanks to the industrial high cell density fermentation processes already developed for its initial application and the use of strong and tightly regulated promoters, as a new heterologous expression system.…”
Section: Yeast: Lessons Learned From Antiquitymentioning
confidence: 99%
“…The final formulation of this vaccine contains L1-based VLPs from the 9-valent HPV serotypes mostly associated with the development of cervical cancer. 23 Recombinant vaccines produced in yeast strains other than S. cerevisiae (so-called non-conventional strains) are of great interest for production of vaccine antigens and immunotherapeutics. One such non-conventional strain is Pichia pastoris, a yeast originally introduced in the 1960s as an additive for animal foods, and later, thanks to the industrial high cell density fermentation processes already developed for its initial application and the use of strong and tightly regulated promoters, as a new heterologous expression system.…”
Section: Yeast: Lessons Learned From Antiquitymentioning
confidence: 99%
“…Our findings are consistent with prelicensure clinical trials in which serious allergic reactions were rare. 35 We detected preliminary statistical signals for syncope in 18-to 26-yearold women, but not in younger girls, a group in which higher rates of syncope have been reported. 36 Our results are in general agreement with both cohort and passive surveillance studies in which researchers have found associations between 4vHPV and vasovagal syncope, particularly among adolescents.…”
Section: Discussionmentioning
confidence: 69%
“…The proportions of pregnancies with adverse outcomes following receipt of the nonavalent vaccine were within ranges reported in the general population. 116 The proportions of participants with live births, difficulty with delivery, spontaneous abortions, and late fetal deaths were similar for nonavalent and quadrivalent vaccine. No congenital anomaly was reported in the case of pregnancies with an estimated date of conception that was within 30 days before or after any vaccination.…”
Section: Pregnancymentioning
confidence: 89%
“…115 For the nonavalent vaccine, the rate of serious adverse events attributable to the vaccine was <0.1%. 116 Comparison of the nonavalent and quadrivalent vaccines yielded rates of serious adverse events of 0.4% and 0.2% respectively. 59 Postlicensure clinical trials on the safety of the quadrivalent and bivalent vaccines in women aged 18-45 years yielded no clinically relevant differences between the vaccinated groups with regard to new onset chronic disease, including new onset autoimmune disease.…”
mentioning
confidence: 99%